Determinants of inconsistent condom use with female sex workers among men attending the STD clinic in Singapore. Issue 4 (4th August 2004) - Wee, S; Barrett, M E; Lian, W M; Jayabaskar, T; Chan, K W R
Abstract : Background/objectives: Female sex workers and their male clients have been identified as risk groups for the transmission of STDs and HIV. Behavioural interventions targeting clients need to address inconsistent condom use among them. The aim of the study is to assess the sociodemographic, behavioural, and psychological factors associated with inconsistent condom use among clients of sex workers. Methods: 229 male patients attending the STD clinic in Singapore who reported paying for sex in the previous 6 months were interviewed. Response rate was 91%. Results: Overall, 45% used condoms inconsistently; these clients were more likely to have poor STD knowledge, visit sex workers five or more times in the past 6 months, have lower self efficacy, less favourable social norms for condom use, and more likely to forget condom use when intoxicated (alcohol impaired decision making). Conclusions: Behavioural interventions for clients need to improve STD/HIV transmission knowledge and focus on improving client's self efficacy in using condoms.